2007
DOI: 10.1176/ajp.2007.164.4.647
|View full text |Cite
|
Sign up to set email alerts
|

Cerebellar Development and Clinical Outcome in Attention Deficit Hyperactivity Disorder

Abstract: Decreased volume of the superior cerebellar vermis appears to represent an important substrate of the fixed, nonprogressive anatomical changes that underlie ADHD. The cerebellar hemispheres constitute a more plastic, state-specific marker that may prove to be a target for clinical intervention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
129
0
3

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 227 publications
(146 citation statements)
references
References 61 publications
11
129
0
3
Order By: Relevance
“…Similarly, slower go signal reaction times in the go/no-go task have been linked to the extent of cerebellar lesions (41). Such human lesion studies implicate the cerebellum in response inhibition, and align with previous reports of subtle cerebellar anatomic anomalies in adults with persistent ADHD(42). Using MEG, we additionally find that ADHD symptoms were associated with cerebellar activity in a time window 500–600 ms after the stop signal.…”
Section: Discussionsupporting
confidence: 86%
“…Similarly, slower go signal reaction times in the go/no-go task have been linked to the extent of cerebellar lesions (41). Such human lesion studies implicate the cerebellum in response inhibition, and align with previous reports of subtle cerebellar anatomic anomalies in adults with persistent ADHD(42). Using MEG, we additionally find that ADHD symptoms were associated with cerebellar activity in a time window 500–600 ms after the stop signal.…”
Section: Discussionsupporting
confidence: 86%
“…Alterations of this phenomenon have been observed in various psychiatric conditions (Mackie et al , 2007) (Jarvis et al , 2008) (Castellanos et al , 2002) (Pujol et al , 2004) (Hill et al , 2003) and in adolescents with familiar history of severe alcohol abuse (Hill et al , 2007). …”
Section: Discussionmentioning
confidence: 99%
“…Several studies, however, have reported significant group differences in conventional volumes of the hippocampus (36), the putamen (45, 46), the globus pallidus (47), the frontal cortex (47, 48), and the cerebellum (47, 49) in youths with ADHD relative to comparison subjects. Thus, examination of both conventional thalamic volumes and morphological features of the thalamic surface is appropriate in the study of ADHD.…”
Section: Discussionmentioning
confidence: 99%